Heavy Metal Levels and Potential Health Risk Assessment in Honey Consumed in the West of Iran - Soheil Sobhanardakani; Mona Kianpour (Hamadan University of Medical Sciences, 2016)
Since the worldwide research on content of heavy metals in honey is narrow, this study was carried out to analyze heavy metals (Cd, Cr, Ni, and Zn) in honey and assess its associated health risk in Hamadan City, Iran, in 2015. Totally, 15 freshly ripened samples of honey were analyzed for heavy metals using ICP-OES with three replications after burning to ash and digesting with dilute nitric acid. The potential health index was then calculated. The results showed that the mean levels of Cd, Cr, Ni, and Zn in the honey samples were 63.18 ± 43.39, 58.05 ± 30.32, 56.15 ± 54.32, and 684.43 ± 190.43 µg kg-1, respectively. Also, the health risk assessment showed no potential risk for children and adults in relation to the consumption of honey in the studied region. According to the results of the current study, although there is no adverse effect for the local population through the consumption of honey, due to the increased discharge of pollutants especially heavy metals into the natural environment, it is very important to assess foodstuff before release to the consumer market.